(untitled) (Alternate Horizons, 2022)
The epidemic of corruption in South Africa and the divisions within our own government are hindering us from executing the UN Secretary-General’s call for 2022 to be the year of recovery for everyone. We must first eradicate our local epidemic before tackling the larger pandemic.